Social determinants of panic buying behaviour amidst Covid-19 pandemic : the role of perceived scarcity and anticipated regret - Tan, Lydia Sonia (Nanyang Technological University, 2021)
Panic buying behaviour is inherently undesirable due to its detrimental impact on the community’s resources and disruptions to supply chain systems. The prevailing Covid-19 pandemic has seen a resurgence of this phenomenon across the world, leaving supermarkets in stockout situations. While panic buying is largely reasoned as a psychological reaction to an extreme event, it is also a socially relevant behaviour, as our perception of a crisis can be shaped by our observations and interactions within society. The social determinants of panic buying behaviour, particularly on how these factors heighten one’s perception of scarcity, and trigger panic buying behaviour, are studied. A theoretical model is developed to explain panic buying behaviour in a social context by synthesising various social and behavioural theories, and the inter-relationship among the latent constructs is analysed using the structural equation modelling approach. Accordingly, an online survey was administered and analysis of the data confirmed that non-coercive social influence, social norm, and observational learning directly influence one’s perception of scarcity. Additionally, perceived scarcity can motivate panic buying behaviour directly or indirectly through feelings of anticipated regret. This study has contributed to the limited literature on panic buying. Understanding the underlying mechanisms of panic buying will aid policymakers and businesses in developing intervention or support strategies to cope with such behaviour.